The Last Plague : Spanish Influenza and the Politics of Public Health in Canada - MARK OSBORNE HUMPHRIES (University of Toronto Press, 2013)
On 27 September 1918, two weeks after his eighteenth birthday, Gunner George William F. fell ill. At first his symptoms were mild: chills, headache, pains all over; a slight cough, a moderate temperature. George William was an underage soldier and had been waiting more than two years to go overseas. All through September, men had been shipping out – some to France, others to Canada’s new mission in Siberia. Colds were common in the Halifax barracks where he was stationed, especially in the autumn months.1 He fought his symptoms for two days as he drilled, marched, and played sports in the chilly autumn rain.2 By the 29th, he had grown considerably worse and he was forced into hospital. There his condition quickly deteriorated. Within a couple of days, his breathing grew shallow and more infrequent as his pulse quickened to 112 beats per minute. His temperature climbed above 103 degrees. Blood dripped from his nose. On 4 October, doctors noted that his lips, fingertips, and earlobes were beginning to turn blue from lack of oxygen. His once slight cough became ‘considerable,’ and he began to complain of chest pain. A mild flu was rapidly progressing into a severe case of pneumonia. Although his doctors still hoped for recovery, his temperature remained high. On the night of 16 October, almost three weeks after entering hospital, his breathing quickened still more, rising above fifty shallow breaths per minute. The young soldier was gasping for air but his lungs were incapable of absorbing oxygen. At five the following morning, Gunner George William F. died from complications of Spanish flu. There was little doctors could do but watch him perish.3